(untitled) (Latakia University Journal -Biological Sciences Series, 2019)
نُفذ البحث بهدف معرفة مدى تحمل نبات الدردار السوري Fraxinus syriaca لتراكيز مختلفة من كلوريد الصوديوم NaCl في ماء الري وكانت النتائج مايلي: تباطأ نمو النباتات بشكل واضح مع ازدياد التركيز الملحي في ماء الري، إذ انخفض مقدار الزيادة الكلية في طول النبات من (13,25) سم في معاملة الشاهد (ري بماء الصنبور)، إلى(2,11) سم في معاملة (3000) جزء بالمليون، وقد أكدت نتائج التحليل الإحصائي تفوق الشاهد على جميع المعاملات الأخرى. وكان النقص النسبي (%84.15-) في معاملة (3000) جزء بالمليون مقارنة مع الشاهد. ازداد محتوى شوارد الكلور والصوديوم في الأوراق والتربة مع زيادة واضحة لنسبة التوصيل الكهربائي (EC) في كل المعاملات. وترافق ذلك بارتفاع واضح في النسبة المئوية للمادة الجافة في الأوراق من 36.51% في معاملة الشاهد إلى 57.3% في معاملة (3000) جزء بالمليون، وانعكس ذلك سلباً على نمو النبات. أدت زيادة تراكيز كلوريد الصوديوم في ماء الري إلى زيادة محتوى الاوراق من كلوروفيل a بشكل واضح حتى المعاملة الرابعة (1500) جزء بالمليون ثم بدأت بالانخفاض قليلاً عند التراكيز الأعلى. أما الكلوروفيل b فقد كانت زيادته واضحة في كل المعاملات. The study was conducted to investigate the extent of Fraxinussyriaca tolerance of different concentrations of sodium chloride salt in irrigation water, and the results were as follows: The growth of the plants slowed down clearly with the increase of Sodium Chloride concentration in irrigation water. The total increase amount in plant length was reduced from (13.25 cm.) in the control treatment (irrigation with tap water only) to (2.11 cm.) in the treatment 3000 ppm. The results of the statistical analysis confirmed that the control surpassed all the other treatments. The relative reduction was (-84.15%) in the treatment 3000 ppm. compared with the control. The content of chloride and sodium ions in leaves and soil was increased with a remarkable increase in electric conductivity (EC) in all treatments. This was accompanied by an increase in the dry matter percentage in leaves from 36.51% in control treatment to 57.3% in (3000 ppm) treatment, and this was reflected negatively on plant growth. The increase of sodium chloride concentrations in irrigation water has led to an increase of leaves’ content of chlorophyll a in anearly way till the fourth treatment (1500 ppm), then it had a little decrease at the higher concentrations, but the increase of chlorophyll (b) was clear in all the treatments.